IMPLEMENTATION OF CLINICAL SUPERVISION WITH A LESSON STUDY APPROACH THROUGH ZOOM MEETING IN IMPROVING TEACHER PROFESSIONALISM - Darwis B (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aims to improve teacher professionalism through the application of clinical supervision with a lesson study approach through zoom meetings in Kampar District, Kampar Regency. This research is action research with the lesson study approach. Research data were collected through questionnaires and observation sheets. The data collected are in the form of teaching simulation scores and the design scores of the Learning Implementation Plan. The research subjects were 36 teachers in Kampar District, Kampar Regency. The research analysis technique used descriptive analysis. The results showed that in the first cycle, the score was 80.08 in the good category, while in the second cycle, the score was 83.85 in the good category. Thus, that the application of clinical supervision with a lesson study approach through zoom meetings that are carried out continuously and consistently results in significant changes in learning improvement and at the same time increasing teacher performance and professionalism.